Mi azaroso camino hacia la historia andina - Sánchez-Albornoz, Nicolás (Pontificia Universidad Católica del Perú, 2020)
The following autobiographic note of the renowned historian Nicolás Sánchez-Albornoz illustrates how life’s different vicissitudes carried him to the field of Andean history. In virtue of his book Trabajo y migración indígenas en los Andes coloniales’ presentation, this recount of the past invites to rethink the historian vocation. It tells us that the specialization pursued will not always be due to genuine personal or academic interests, but to different political, geographical, and temporal circumstances.

La siguiente nota autobiográfica del reconocido historiador Nicolás Sánchez-Albornoz ilustra cómo las distintas vicisitudes de la vida lo llevaron al campo de la historia andina. Con la excusa de la presentación de libro Trabajo y migración indígenas en los Andes coloniales, esta mirada al pasado invita a replantear la vocación del historiador, pues la especialización temática no siempre se deberá a genuinos intereses personales o académicos, sino a distintas circunstancias políticas, geográficas y temporales.
My unsteady road towards Andean history
Keywords: Sánchez-Albornoz; Andean History; Historian; Vocation; Sánchez-Albornoz; Historia andina; Historiador; Vocación; https://purl.org/pe-repo/ocde/ford#6.01.01